Rancang Bangun Sistem Manajemen Gudang Berbasis Web Menggunakan Algoritma FEFO dan Basis Data NoSQL untuk Optimalisasi Akurasi Stok - Andre; Firstiansyah, Najwan Caesar (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
The poInventory management efficiency and data accuracy are critical factors in logistics operations. Classicissues such as the accumulation of expired goods (dead stock), physical stock discrepancies, and delays inreturn handling frequently occur due to manual spreadsheet-based recording methods. This study aims to designand build a web-based Warehouse Management System (WMS) integrating the Laravel framework with NoSQLdatabase technology (Firestore) to accelerate data access. The system implements automatic stock allocationalgorithms based on First-Expired-First-Out (FEFO) and First-In-First-Out (FIFO), a capacity validationfeature (Gatekeeper), and a Closed-Loop Return mechanism for return tracking. The testing method employedblack-box testing and operational performance comparative analysis. The results indicate that the systemimplementation improved stock accuracy from 85% to 98%. Furthermore, item search time efficiency increasedsignificantly by 6,000% (from 120 seconds to 2 seconds) due to the NoSQL data structure. The Gatekeeperfeature proved valid in rejecting inbound transactions during overcapacity, while the FEFO algorithmsuccessfully prioritized the issuance of goods nearing expiration automatically. This study concludes that digitaltransformation through WMS can minimize human error and enhance warehouse operational speed in real-time